(untitled) (Circe de clásicos y modernos, 2026)
Ovid’s Heroide 15 (Sappho to Phaon) enacts a strong break with the letters that precede and follow it in the collection because of the historical nature of its writer. Given the uniqueness of Sappho in the whole text, I analyze the reconversion of the Greek figure into the Latin generic context. I point out some possible intertextualities with the work we have preserved from the Greek historical female writer in order to trace the changes that allowed the poet to adapt his character into his new elegiac and epistolary context.